2021
DOI: 10.48550/arxiv.2108.03190
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantum Quantile Mechanics: Solving Stochastic Differential Equations for Generating Time-Series

Annie E. Paine,
Vincent E. Elfving,
Oleksandr Kyriienko

Abstract: We propose a quantum algorithm for sampling from a solution of stochastic differential equations (SDEs). Using differentiable quantum circuits (DQCs) with a feature map encoding of latent variables, we represent the quantile function for an underlying probability distribution and extract samples as DQC expectation values. Using quantile mechanics we propagate the system in time, thereby allowing for time-series generation. We test the method by simulating the Ornstein-Uhlenbeck process and sampling at times di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 90 publications
(129 reference statements)
0
7
0
Order By: Relevance
“…One option is to use a t-dependent feature map for parameterizing the model. For instance, we employed it successfully in DQC-based quantum function propagation [28]. In this case, it is convenient to use an identity-valued feature map at t 0 , and learn to adjust angles as t deviates from t 0 .…”
Section: Model Differentiation and Constrained Training From Stochast...mentioning
confidence: 99%
See 4 more Smart Citations
“…One option is to use a t-dependent feature map for parameterizing the model. For instance, we employed it successfully in DQC-based quantum function propagation [28]. In this case, it is convenient to use an identity-valued feature map at t 0 , and learn to adjust angles as t deviates from t 0 .…”
Section: Model Differentiation and Constrained Training From Stochast...mentioning
confidence: 99%
“…In Ref. [28] we have shown that initialization with lowdegree polynomial (truncated Chebyshev series) can vastly reduce number of optimization epochs. Here, we propose to use the structure of the quantum model in Eq.…”
Section: Fourier Initializationmentioning
confidence: 99%
See 3 more Smart Citations